Dynamics and response of microbial diversity to nutritional conditions in denitrifying bioreactor for linear alkylbenzene sulfonate removal. (1st June 2020) - Andrade, Marcus Vinicius Freire; Delforno, Tiago Palladino; Sakamoto, Isabel Kimiko; Silva, Edson Luiz; Varesche, Maria Bernadete Amâncio
Abstract: The aim of this study was to evaluate the microbial structure and phylogenetic diversity under the influence of nutritional conditions and hydraulic retention time (HRT) in fluidized bed reactors (FBR), operated in short HRT (8 h – FBR8; 12 h – FBR12) for linear alkylbenzene sulfonate (LAS) removal from laundry wastewater. After each phase, biofilm samples from FBR8 and FBR12 were submitted to microbial sequencing by Mi-Seq Illumina®. Higher LAS removal rates were observed after 313 days, achieving 99 ± 3% in FBR12 (22.5 ± 5.9 mg LAS/L affluent) and 93 ± 12% in FBR8 (20.6 ± 4.4 mg LAS/L affluent). Different modifications involving genera of bacteria were observed throughout the reactors operation. The identified microorganisms were, mostly, related to LAS degradation and nitrogen conversion such as Dechloromonas, Flavobacterium, Pseudomonas, and Zoogloea . Highlights: Hydraulic retention time affected the microbial community establishment. Nitrate and ethanol addition induced microbial shifts in diverse taxonomical level. Laundry wastewater addition influenced on microbial stratification. Several genera related to LAS degradation were identified in both reactors.